Self-Management Strategies Used by Older Hispanic Women to Overcome Functional Disabilities. (4th July 2020) - Orellano-Colón, Elsa M.; Abdalla-Mukhaimer, Nelly; Rodríguez-Ramos, Bryan A.; Rodríguez-Robles, Rebecca; Rivero-Méndez, Marta; Lizama-Troncoso, Mauricio; Jutai, Jeffrey W.; Jiménez-Velázquez, Ivonne Z.; Varas-Díaz, Nelson; Hallman-Navarro, Deanna
Abstract: Aims: To gain a deep understanding of the person, environment, and occupation-related self-management strategies used to overcome disabilities in daily living activities. Methods: In this concurrent transformative mixed method design guided by the Person, Environment, Occupation-Performance Model we assessed 12 older women functional disabilities using the PROMIS Physical Function Short Form 20, followed by in-depth interviews about their strategies for dealing with these disabilities. Results: The sample's PROMIS mean T-score was below the national average. The sample predominantly used occupation-related strategies to overcome difficulties in daily living activities and these strategies were moderated by personal and cultural factors such as psychological and spirituality. The most frequently used strategy for self-care and instrumental activities of daily living were changing the method of performance and activity pacing for functional mobility. Conclusions: The strategies used by these participants can be used for the development of disability self-management interventions to increase Hispanic woman's function.